The Development of Video on Pickled Fruit Production for Flipped Classroom - Anggraeni, Andian Ari; Sumaryana, Sumaryana; Rinawati, Wika; Murniati, Dewi Eka (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Undergraduate students are categorized as Generation Z. They prefer learning using video rather than the book. Demonstration videos are suitable for productive courses because they show step by step of product making. This study aimed to 1) develop a video of pickled fruit production for the Food Preservation Technology course, Universitas Negeri Yogyakarta (UNY), Indonesia and 2) determine the video's feasibility. This study was a research and development (R&D) performed by ten steps, namely information collecting, planning, developing initial products, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, as well as dissemination and implementation. Data analysis was performed descriptively. The video feasibility analysis was conducted by one material expert, one media expert, two teachers, two peer reviewers, four students in one-on-one testing, and 36 students in classroom testing. Based on the feasibility test, the video was declared very feasible as learning media. Text, images, animations, and effects appeared in several parts of the video, making it easier for the students to understand the content. This video can be embedded in the learning management system (LMS) such as Google Classroom, Moodle, and others to facilitate mobile learning, and implemented in a flipped classroom design. Pre-test and post-test were then performed on 29 students in operational field testing. The post-test was significantly higher than the pre-test (p<0.05), so the video was able to improve the students' cognitive skills.